ANALISIS PERILAKU PEMBELIAN OBAT-OBATAN HALAL DI PROVINSI JAWA TENGAH - Edris, Mochamad (Research Center and Case Clearing House PPM School of Management, 2020)
This study aims to analyze purchasing behavior and to determine the most dominant factor influencing purchase intention of halal labeled medicines of Muslim consumers in Central Java. Sample of 244 respondents are used in this study. Data is collected using questionnaire with judgment sampling technique and analyzed using the Structural Equation Modeling technique using AMOS. Theory of Planned Behavior model is used to identify factors influence purchasing decision and behavior. Today's society pays little attention to the halal label when buying and or consuming medicine and food products. The results of the study found that subjective norms, attitudes, and behavioral control perceptions have an influence on consumer purchase intentions to buy halal labeled medicines. Subjective norms have the most dominant influence on purchase intentions. Furthermore, subjective norms have a significant effect on consumer attitudes toward halal labeled medicines. This results show that significant people around consumer or social environment factors such as family and friends have a strong influence in consumer purchasing decision making. This study supports the previous research on consumer purchase intention.